Normal and Pathological Tau Uptake Mediated by M1/M3 Muscarinic Receptors Promotes Opposite Neuronal Changes - Morozova, Viktoriya; Cohen, Leah S.; Makki, Ali El-Hadi; Shur, Alison; Pilar, Guillermo; El Idrissi, Abdeslem; Alonso, Alejandra D. (Frontiers in Cellular Neuroscience, 2019)
The microtubule associated protein tau is mainly found in the cell’s cytosol but recently it wasalso shownin the extracellular space. In neurodegenerative diseases, like Alzheimer’s Disease (AD), pathological tau spreads from neuron to neuron enhancing neurodegeneration. Here we show that HEK293 cells and neurons in culture uptake extracellular normal and pathological Tau. Muscarinic receptor antagonists atropine and pirenzipene block 80% this uptake. CHO cells do not express these receptors therefore cannot uptake tau, unless transfected with M1 and/or M3 receptor. These results strongly suggest that muscarinic receptors mediate this process. Uptake of normal tau in neurons enhances neuronal process formation but a pseudophosphorylated form of tau (pathological human tau, PH-Tau) disrupts them and accumulates in the somatodendritic compartment. AD hyperphosphorylated tau (AD P-Tau) has similar effects as PH-Tau on cultured neurons. Addition of either PH-Tau or AD P-tau to neuronal cultures induced microglial activation. In conclusion, uptake of extracellular tau is mediated by muscarinic receptors with opposite effects: normal tau stabilizes neurites; whereas pathological tau disrupts this process leading to neurodegeneration.